Community Service in the Perspective of Social Innovation: Efforts to Enhance Value Added and Competitiveness of MSMEs - Frans Sudirjo; Lili Fadli Muhamad; Dewa Oka Suparwata (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
This study aims to enrich the literature on community service by examining the role of social innovation in enhancing value added and the competitiveness of Micro, Small, and Medium Enterprises (MSMEs). The study employs a qualitative approach using a literature review method and descriptive analysis. Data were collected from various sources, including Google Scholar and credible websites, covering the period from 1994 to 2026. From an initial pool of 50 articles, a rigorous selection process based on relevance and quality resulted in 31 articles for further analysis. The findings indicate that community service based on social innovation can enhance MSME capacity through participatory approaches, cross-sector collaboration, and the utilization of digital technology. The integration of theories such as Social Innovation Theory, Participatory Development Theory, and the Resource-Based View reinforces that program success is determined by active community involvement and the strengthening of innovation ecosystems. Furthermore, the analyzed case studies show that social innovation can increase product value added, expand market access, and sustainably strengthen MSME competitiveness. This study is expected to contribute to the development of more innovative, inclusive, and adaptive community service models in response to economic dynamics.